Ethical issues in taking neuroscience research from bench to bedside - Leshner, Alan I (Cerebrum (New York, NY), 2004)
Dramatic advances in neuroscience have created fast-rising expectations for improvements in the health and well-being of people around the world. But fulfilling this promise is proving to be neither quick nor easy, and not for scientific reasons alone. Alan Leshner urges that neuroscientists not only address the significant challenges of their own investigations but also be willing to participate in ethical and legal dialogues with colleagues and non-colleagues alike.